STRATEGI MEMAHAMI TEKS PIDATO BAHASA INGGRIS DENGAN METODE THINK ALOUD PROTOCOLS (TAPs) - SULISTYANINGRUM, SITI DRIVOKA (JURNAL PENDIDIKAN BAHASA DAN SASTRA, 2011)
In the process of translating, the translator sometimes has different approaches to acquire the ideal translation. Nevertheless, the initial step and the most natural way for translator, either beginner or expert, to translate is by using the Think Aloud Protocols (TAPs). In this step, we are trying to translate a text or phrase spontaneously based on our knowledge and insight. In general, this study is to gain a better understanding of the psychological and linguistic mechanism involved in the activity of translating. Hence, this study emerges two main questions namely: (1) What kind of the decision making that commonly used in process that the translators commit and (2) In what kind of event that the pauses, hesitation, and the alteration do occurs. This leads to the idea that the study covers the discussion on the kind of decision making that translators commit when translating particular text given and at the same time will strictly focus on the pauses, hesitation, and the alteration when translating it. The research employed descriptive analytical method. The writer began by collecting data based on recording data of target interviewee, in this matter the translator. The classification of the data is based on the mental process made by translator namely: pause, alteration, and hesitation.Â  The study resulted several finding namely there are 22 or 48% pauses , 12 or 29% alteration, and 8 or 19%hesitations, so there are 25 mental process occurred this ext. Based on the types of target language, the data shows different when it comes to the target text from English to or vice versa. The percentage of alteration from Bahasa to English is higherÂ  (42.73%) than English to Bahasa (31.82%). It indicates that the translator have difficulty to make adequate word or create fluent verbalization. While from English to Bahasa the result shows different. As a matter a fact, the percentage of this target language type for pause shows higher value than English to Bahasa which is 50% or 22 pauses. It indicates that the translator have less trouble to make adequate word or create fluent verbalization. The translator also put very much attention in the quality of the product by always thinking it deep.Keywords: Think Aloud Protocol (TAPs) method, memahami teks, speech.